(untitled) (Pragyaratna प्रज्ञारत्न, 2023)
Integrating educational technology in mathematics education has emerged as a transformative force revolutionizing traditional teaching/ learning(T/L) practices. Understanding mathematics teachers’ perceptions regarding technology integration is vital in fostering successful adoption and implementation in their T/L practice. Utilizing a structured questionnaire with Likert-scale items, the study gathered data on teachers’ perceptions of technology’s effectiveness and its impact on student learning outcomes. The findings revealed highly positive perceptions among mathematics teachers, with mean scores ranging from 3.73 to 4.33 and statistically significant p-values (p < 0.05). Moreover, the study found no significant differences in various perceptions based on gender, academic level, teaching experience, or level of teaching. The results emphasize the potential benefits of incorporating educational technology in mathematics education and provide valuable insights for stakeholders seeking to enhance mathematics learning experiences at Mahendra Ratna Campus and beyond.